Turning Doctors Into Employees - Anderson, Matthew (Radical Teacher, 2014)
Background: Much of the contentious debate surrounding the Patient Protection and Affordable Care Act (“Obamacare”) concerned its financing and its attempt to guarantee (near) universal access to healthcare through the private insurance market. Aside from sensationalist stories of “death panels,” much less attention went to implications of the bill for the actual provision of healthcare. Methodology: This paper examines the "patient-centered medical home" (PCMH) model which has been widely promoted as a means of reviving and improving primary care (i.e. general internal medicine, family medicine, and pediatrics). Argument: The PCMH and many of its components (e.g pay-for-performance, electronic medical records) were interventions that were implemented on a massive basis without any evidence of benefit. Recent research has not generally supported clinical benefits with the PCMH model. Instead it seems to designed to de-professionalize (make proletarians of) health care workers and enforce corporate models of health. The core values of professional work are undermined while the PCMH does nothing to address the structural marginalization of primary care within US health care. Conclusions: The development of alternative models will require political changes. Both doctors and teachers are in a position of advocate for more progressive systems of care and education.